Garden mandalas - Jones, Jean L., author; Dietemann, David L., advisor; Yust, Dave, 1939-, committee member; Lundberg, Thomas R., committee member; Macagno-Shang, Laura, committee member (Colorado State University. Libraries, 1995)
Since my early childhood I have had a dialogue with nature; these works come from my side of that relationship. While they reflect my interpretation of a specific form of plant life, they also symbolically illuminate my inner world-my journey through self-knowing. This symbolism influences the subject matter, size of the work and the choice and handling of the medium. The symbols evoked by the garden are revealed in the studio. My time in the garden is a visual feast, my imagery chosen intuitively for its formal challenges and metaphoric potential. I look for plants full of pattern, color and movement that emerge from the darkness to touch the senses and celebrate the light.
Keywords: Symbolism; Watercolor painting; Nature